Morton City, Hodgeman County - Brown, Theodore (Kansas State University, The Chapman Center for Rural Studies, 2010)
Theodore Brown traces the origins of the little-studied Hodgeman County Exoduster settlement. Using archival material from Jetmore Museum and his own family history, he documents the stone masonry skills brought to western Kansas by former slaves in the 1880s. He includes photographs of the few remaining stone structures built by African-American settlers in the harsh, arid environment of the plains.
Theodore Brown, “Morton City, Hodgeman County ,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/12.
Keywords: African American; Exodusters; Hodgeman County; Morton City; Stone Masonery; Theodore Brown